The effects of NDM-5 on Escherichia coli and the screening of interacting proteins - Li, Lin; Gao, Yiming; Wang, Longbo; Lu, Fang; Ji, Qianyu; Zhang, Yanfang; Yang, Shuo; Cheng, Ping; Sun, Feifei; Qu, Shaoqi (Frontiers in Microbiology, 2024)
Carbapenem-resistant Escherichia coli (E. coli) strains are widely distributed and spreading rapidly, creating significant challenges for clinical therapeutics. NDM-5, a novel mutant of New Delhi Metallo-β-Lactamase-1 (NDM-1), exhibits high hydrolase activity towards carbapenems. Since the genetic backgrounds of clinically isolated carbapenem-resistant E. coli are heterogeneous, it is difficult to accurately evaluate the impact of blaNDM-5 on antibiotic resistance. Herein, E. coli BL21 was transformed with a plasmid harbouring blaNDM-5, and the resultant strain was named BL21 (pET-28a-blaNDM-5). Consistent with the findings of previous studies, the introduction of exogenous blaNDM-5 resulted in markedly greater resistance of E. coli to multiple βlactam antibiotics. Compared with BL21 (pET-28a), BL21 (pET-28a-blaNDM-5) exhibited reduced motility but a significant increase in biofilm formation capacity. Furthermore, transcriptome sequencing was conducted to compare the transcriptional differences between BL21 (pET-28a) and BL21 (pET-28a-blaNDM-5). A total of 461 differentially expressed genes were identified, including those related to antibiotic resistance, such as genes associated with the active efflux system (yddA, mcbR and emrY), pili (csgC, csgF and fimD), biofilm formation (csgD, csgB and ecpR) and antioxidant processes (nuoG). Finally, the pGS21a plasmid harbouring blaNDM-5 was transformed into E. coli Rosetta2, after which the expression of the NDM-5 protein was induced using isopropyl-β-D-thiogalactoside (IPTG). Using glutathione-Stransferase (GST) pull-down assays, total proteins from E. coli were scanned to screen out 82 proteins that potentially interacted with NDM-5. Our findings provide new insight into the identified proteins to identify potential antibiotic targets and design novel inhibitors of carbapenem-resistant bacteria.